Marital status and biological condition of Polish males - Lipowicz, Anna (Anthropological Review, 2001)
Strong evidence for marital differences in mortality has been demonstrated in a large number of countries. Married men and women have lower death rates than unmarried individuals within each adult age group. Additionally, married persons tend to be healthier as compared to unmarried. In the literature two explanations for this patterning have been proposed. .The health selection hypothesis. suggested that disabled or less healthy people are not as likely to get married as the healthy ones. In .the social causation hypothesis ., marriage yields health benefits through emotional and social support which may act as a buffer against the effects of life stress. In this study, .the social causation hypothesis. is supported.